A core outcome set for future male infertility research: development of an international consensus - Rimmer, Michael P; Howie, Ruth A; Anderson, Richard A; Barratt; Christopher L R; Barnhart, Kurt T; Beebeejaun, Yusuf; Bertolla, Ricardo Pimenta; Bortoletto, Pietro; Brannigan, Robert E; Cantineau; Astrid E P; et al. (Oxford University Press (OUP), 2025)
Study question: Can a core outcome set be developed through a global consensus to standardize outcome selection, collection, comparison, and reporting in future male infertility trials?
Summary answer: A minimum dataset, known as a 'core outcome set', has been developed for randomized controlled trials (RCTs) and systematic reviews evaluating potential interventions for male infertility.
What is known already: Numerous factors, including a failure to consider the perspectives of men with lived experiences of infertility or their partners when developing and conducting RCTs can limit their clinical utility. Selection of outcomes, variations in outcome definitions, and the selective reporting of outcomes based on statistical analysis make the results of infertility research challenging to interpret, compare, and implement. For male infertility, this is further compounded by there being potentially three participants, the male, their female partner, and any offspring born, all with outcomes to be reported. This has led to significant heterogeneity in trial design and reporting. While a core outcome set for general infertility trials has been developed, there is no such outcome set for male infertility trials.
Study design, size, duration: A two-round Delphi survey (334 participants from 39 countries) and consensus development workshops (44 participants from 21 countries).
Participants/materials, setting, methods: Healthcare professionals, researchers, and men and women with infertility were brought together in a transparent process using formal consensus science methods.
Main results and the role of chance: The core outcome set for male infertility trials has been developed by the inclusion of specific male-factor outcomes in addition to the general infertility core outcome set. These outcomes include assessment of semen using the World Health Organization recommendations for semen analysis; viable intrauterine pregnancy confirmed by ultrasound (accounting for singleton, twin, and higher multiple pregnancies); pregnancy loss (accounting for ectopic pregnancy, miscarriage, stillbirth, and termination of pregnancy); live birth; gestational age at delivery; birthweight; neonatal mortality; and major congenital anomaly. Although not a requirement as part of the core outcome set, other outcomes were identified as potentially useful in certain study settings.
Limitations, reasons for caution: We used consensus development methods in this work, which have inherent limitations, including the representativeness of the participant sample, Delphi survey attrition, and an arbitrary consensus threshold.
Wider implications of the findings: Embedding the core outcome set within RCTs and systematic reviews should ensure the comprehensive selection, collection, and reporting of core outcomes, which are inconsistently reported at present. Research funding bodies, the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) statement, and over 80 specialty journals, including the Cochrane Gynaecology and Fertility Group, Fertility and Sterility and Human Reproduction, have committed to implementing this core outcome set for male infertility trials.
Study funding/competing interest(s): This work was funded by The Urology Foundation, Small Project Fund awarded to Michael P Rimmer at the University of Edinburgh, UK. RTM was supported by a United Kingdom Research and Innovation (UKRI) Future Leaders Fellowship (MR/Y011783/1). C.L.R.B. is the co-editor in chief of Human Reproduction and recipient of a BMGF grant and received consultancy fees from Exscentia and Exceed sperm testing, paid to the University of Dundee and speaking fees or honoraria paid personally by Ferring, Copper Surgical and RBMO. R.P.B. receives royalties from Flow diagnósticos. M.L.E. is an advisor to the companies Hannah, Illumicell, Next, Legacy, Doveras, Vseat and received a consultancy fee for this. B.W.M. is a paid consultant for Norgine and Organon and has received research funding from Ferring and Merck, he also receives consultancy and travel support from Merck. R.R.H. received royalties from Elsevier for a book, consultancy fees from Glyciome, and presentation fees from GryNumber Health and Aytu Bioscience. Attendance at Fertility 2020 and Roadshow South Africa by Ralf Henkel was funded by LogixX Pharma Ltd. R.R.H. is also Editor in Chief of Andrologia and has been an employee of LogixX Pharma Ltd. since 2020. M.S.K. has been an associate editor with Human Reproduction Open. K.Mc.E. received funding to attend Fertility 2025 by the British Fertility Society and is the Chair of the British Fertility Society. He is a member of the HFEA's Scientific and Clinical Advances Advisory Committee and a Committee Member of the NICE Fertility Problems Guideline Group. M.H.V.L. receives consultation fees for the WHO Manual Spanish translation, and travel expenses for the ESHRE MRHI meeting in Budapest. She is a member of the editorial board for Fertility & Sterility, F&S Science, Human Reproduction, and Frontiers in Endocrinology. She is also a panel member of the World Health Organization (WHO) Human Reproduction Programme (HRP) Research Project Review Panel. R.S.M. is a member of the NICE Guideline Committee on Fertility and former chair of the British Fertility Society. A. Perheentupa receives an honoraria for lecturing from Merck for the Tackling Infertility manifest, Gedeon Richter & Ferring. A. Perheentupa declares lecture honoraria from Merck, Gideon Richter, and Ferring; and payment from Merck for the Tackling Infertility manifesto. A. Pacey receives consultancy fees for Carrot Fertility and Cryos International as well as lecturing for IBSA Institut Biochimique SA and Mealis Group-all fees paid to The University of Manchester. He is also a Trustee of Progress Educational. Trust (Charity Number 1139856) and Chairman of UKNEQAS Reproductive Sciences Advisory Committee. F.T. is the recipient of a Bayer research grant, as well as DFG Clinical Research Unit 'Male Germ Cells' (CRU326, project number 329621271) and BMBF Junior Scientist Research Centre 'ReproTrack.MS' (grant 01GR2303), he has received travel support from IBSA and Organon. M.v.W. is the Editor-in-Chief of Human Reproduction Update. R.W. is a former Deputy Editor of Human Reproduction and is currently a Deputy Editor of Human Reproduction Update.
Trial registration number: Core Outcome Measures in Effectiveness Trials (COMET) initiative registration No: 1586. Available at www.comet-initiative.org/Studies/Details/1586.